2021
DOI: 10.2478/emj-2021-0031
|View full text |Cite
|
Sign up to set email alerts
|

Determination of black spots by using accident equivalent number and upper control limit on rural roads of Thailand

Abstract: The Department of Rural Roads (DRR) is one of the highway authorities in Thailand responsible for over 48 000 kilometres of rural roads and highway networks. One of its responsibilities is to provide better road safety management. In road safety procedures, black spots are usually identified by observing the frequency of accidents at a particular road section. This research aims to develop a model that includes levels of accident severity in the black spot identification process. The classification of severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In this study CMFs for some of the treatments that are available in the HSM and were used to identify their effects. However, for some others, the CMF is not offered nonetheless a trend about the possible change in crashes or human behavior is identified [9]. Treatments that were used are categorized into four categories; treatments related to intersection types, treatments related to intersection design elements, treatments associated to traffic control and operational elements of intersections and treatments associated to access management.…”
Section: Countermeasures For Hclmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study CMFs for some of the treatments that are available in the HSM and were used to identify their effects. However, for some others, the CMF is not offered nonetheless a trend about the possible change in crashes or human behavior is identified [9]. Treatments that were used are categorized into four categories; treatments related to intersection types, treatments related to intersection design elements, treatments associated to traffic control and operational elements of intersections and treatments associated to access management.…”
Section: Countermeasures For Hclmentioning
confidence: 99%
“…For this model the authors collected the crash data from five rural roads in Thailand during three years. The results showed that most crashes were rear-end type due to exceeded speed limits based on the results of black spots recognized in the study [9]. Erdogan et al (2008) conducted a study in Turkey to assess crash distribution in a highway in Afyonkarashiasar city.…”
Section: Introductionmentioning
confidence: 99%